CREATIVE THINKING ABILITY OF PGSD STUDENTS IN COMPLETING A CLASS ACTION RESEARCH PROPOSAL - Murniningsih; Arif Bintoro Johan; Ani Widyawati; Rully Widyanti Eka Putri (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract Increasing teachers’ professionalism and educational quality in Indonesia can be done through classroom action research (CAR). However, many teachers still have not been able to carry out CAR. As prospective teachers, PGSD students of Sarjanawiyata Tamansiswa University must take the CAR course. The purpose of this study is to measure the ability of students' creative thinking in designing CAR proposals as an effort to evaluate materials to prepare prospective professional teachers. This research is quantitative research analyzed with descriptive statistics. The sample was taken from PGSD students who attended the CAR lecture. Data collection techniques in this study were carried out by analyzing CAR proposals to determine students' creative thinking skills in preparing CAR planning. This study produced information on student knowledge in the form of creative thinking skills with the creative category in terms of problem identification, determining the causes of problems, ideas of action, details of procedures, data analysis, and the ability to design research instruments that still need to be improved.